Attitudes of public elementary school teachers in Zamboanga del Sur toward in-service education practices in that division. - Paulo, Lorenzo 1908- (Quezon City s.n., 1960)
The purpose of the study is to determine the attitude of public elementary school teachers in the Division of Zamboanga del Sur toward the in-service education practices in that division and what they like and dislike about these practices. Also, the research sought to identify the in-service practices in Zamboanga del Sur that public elementary school teachers in that division consider as effective or ineffective and the reasons why they consider these practices as such.
Keywords: Teachers -- Zamboanga del Sur; Employees, Trainingf of